Terorisme: Antara Kolonialisme dan Fundamentalisme - - Miftahuddin (Millah: Journal of Religious Studies, 2006)
Terrorism which is also known as violence and repressiveness up until today is still being an actual issue around the world. Even though, the symptoms of violence, discourtesy, cruelty, and inhumanity cases are actually as old as the history of men. Why does terrorism then emerges, and then are there any approaches available at least to decrease this disease, will be examined in this paper. After any studies had been conducted, terrorism becomes disease of society nowadays, at first it appears because of greedy that develops to colonialism, second appear from "Islam " fundamentalism, which basically is the counter of, colonialism impact. There is one offer to decrease this terrorism with supreme dialogue culture for all people, which can be creating the new fair international order. However, there are some foundations of respecting plurality or multiculturalism of human rights which have to be obeyed in order to have a dialogue.